2015
DOI: 10.1371/journal.pone.0137143
|View full text |Cite
|
Sign up to set email alerts
|

Livestock-Associated Methicillin Resistant and Methicillin Susceptible Staphylococcus aureus Sequence Type (CC)1 in European Farmed Animals: High Genetic Relatedness of Isolates from Italian Cattle Herds and Humans

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) Sequence Type (ST)1, Clonal Complex(CC)1, SCCmec V is one of the major Livestock-Associated (LA-) lineages in pig farming industry in Italy and is associated with pigs in other European countries. Recently, it has been increasingly detected in Italian dairy cattle herds. The aim of this study was to analyse the differences between ST1 MRSA and methicillin-susceptible S. aureus (MSSA) from cattle and pig herds in Italy and Europe and human isolates. Sixty-tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 30 publications
6
82
2
3
Order By: Relevance
“…This differs from what has been observed for CC1 LA-MRSA isolates from Italian dairy cattle, which are closely related and most likely derived from a human CC1 SCCmec IVa lineage (33). This may also indicate that the CC97 MRSA strains are unlikely to have originated from humanto-cattle spillback.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…This differs from what has been observed for CC1 LA-MRSA isolates from Italian dairy cattle, which are closely related and most likely derived from a human CC1 SCCmec IVa lineage (33). This may also indicate that the CC97 MRSA strains are unlikely to have originated from humanto-cattle spillback.…”
Section: Discussioncontrasting
confidence: 79%
“…One MSSA isolate (ST97) from dairy cattle carried the LukM and LukF-PV(P83) genes encoding the highly active bicomponent leukocidin typical of S. aureus strains from cattle and ruminants (24). All isolates carried the hemolysin genes hlb, hl, and hlIII (hl and hlIII coding for a putative membrane protein [33]), and all but three cattle isolates were also positive for hla.…”
Section: Resultsmentioning
confidence: 99%
“…CC1/ST1 is one of the major clones circulating in Italy, where it first was reported in pigs [87,88] and dairy cows [43], and seems to be spreading to other countries. In 2009, one strain was detected in Denmark [89], and recently a few strains were discovered in veal calves and pigs in Belgium [29•].…”
Section: Cc1mentioning
confidence: 99%
“…Fortunately, to date and to our knowledge, PVL-positive MRSA CC1 isolates have not yet been isolated from animals; however, typically present are the IEC genes sak and scn, or the enterotoxine gene sea as in human strains, and they also may carry β-hemolysins, LukFLukS, LukD-LukE, LukX-LukY γ-hemolysin, enterotoxin H, and superantigen X [87,90]. The typical strain found in animals belongs to spa type t127 [43,[87][88][89]. MRSA CC1 also has been implicated in mastitis in cows in Italy [43,90].…”
Section: Cc1mentioning
confidence: 99%
“…Although some studies suggested that the MRSA present in catle is bovine-speciic, most of the reports indicated that MRSA found in catle were derived from humans [89,92,115,116]. Bovine, porcine, canine, feline, and equine MRSA isolates containing the pvl gene and other virulence factors, such as chp, scn, seb, sek, and seq, toxic shock syndrome toxin 1 (tsst1 or tst) gene [91,117], hemolysin, protease, superantigen-like protein, capsule, and bioilm-associated genes [118][119][120][121], may pose a potential threat to public health. …”
Section: Introductionmentioning
confidence: 99%